Projeto integrador nos projetos pedagógicos de curso : uma proposta metodológica para a UFES - Rabello, Sylvia Gonçalves (2018)
Over the years, not only has society changed but also the role that the University plays within it, and for this, the teaching-learning processes also has to evolve in order to supply not only the market, but also the expectations of the students nowadays. In this this context, the University needs to be prepared to offer students the training they need to achieve their personal and professional longings. The present research seeks to answer the following research problem: how are the UFES undergraduate courses in the area of Applied Social Sciences of the Centro de Ciências Jurídicas e Econômicas, in relation to the interdisciplinary activities in their Pedagogical Projects of Courses (PPCs)? Thus, it was defined as a general objective, to study the situation of these courses regarding the activities of an interdisciplinary nature in their PPCs and curricular matrices and, consequently, the following specific objectives: to analyze the situation of undergraduate courses of the Centro de Ciências Jurídicas e Econômicas of UFES, within the area of knowledge Applied Social Sciences regarding the interdisciplinary character activities in their pedagogical projects; mapping the situation of the curriculum of these courses, as to the insertion of interdisciplinary activities of character, required by current norms; to propose an integrator project for Pedagogical Projects of Courses. The research approach adopted was qualitative in nature. The data collection was done by using documental, descriptive and bibliographic research modalities. The data analysis showed that interdisciplinarity is a guideline widely charged by the legislation adopted by UFES, to achieve the PPCs of the courses. The analysis of the PPCs and curriculum of the courses studied showed that none of them clearly brings in their scope the way that interdisciplinarity is operationalized.